Policy stakeholder perspectives on barriers and facilitators to launching a community-wide mass drug administration program for soil-transmitted helminths - Amy Roll; Malvika Saxena; Elizabeth Orlan; Angelin Titus; Sanjay Kamlakar Juvekar; Marie-Claire; Euripide Avokpaho; Félicien Chabi; Comlanvi Innocent Togbevi; Abiguel Belou Elijan; Providence Nindi; Judd L. Walson; et al. (BMC, 2022)
Abstract Background Recent evidence suggests that soil-transmitted helminth (STH) transmission interruption may be feasible through community-wide mass drug administration (cMDA) that deworms community members of all ages. A change from school-based deworming to cMDA will require reconfiguring of STH programs in endemic countries. We conducted formative qualitative research in Benin, India, and Malawi to identify barriers and facilitators to successfully launching a cMDA program from the policy-stakeholder perspective. Methods We conducted 40 key informant interviews with policy stakeholders identified as critical change agents at national, state/district, and sub-district levels. Participants included World Health Organization country office staff, implementing partners, and national and sub-national government officials. We used the Consolidated Framework for Implementation Research to guide data collection, coding, and analysis. Heat maps were used to organize coded data and differentiate perceived facilitators and barriers to launching cMDA by stakeholder. Results Key facilitators to launching a cMDA program included availability of high-quality, tailored sensitization materials, and human and material resources that could be leveraged from previous MDA campaigns. Key barriers included the potential to overburden existing health workers, uncertainty of external funding to sustain a cMDA program, and concerns about weak intragovernmental coordination to implement cMDA. Cross-cutting themes included the need for rigorous trial evidence on STH transmission interruption to gain confidence in cMDA, and implementation evidence to effectively operationalize cMDA. Importantly, if policy stakeholders anticipate a cMDA program cannot be sustained due to cost and human resource barriers in the long term they may be less likely to support the launch of a program in the short term. Conclusions Overall, policy stakeholders were optimistic about implementing cMDA primarily because they believe that the tools necessary to successfully implement cMDA are already available. Policy stakeholders in this study were cautiously optimistic about launching cMDA to achieve STH transmission interruption and believe that it is feasible to implement. However, launching cMDA as an alternative policy to school-based deworming will require addressing key resource and evidence barriers. Trial registration This study was registered in the U.S. National Library of Medicine Clinical Trials registry (NCT03014167).